The Genealogy of Jeconiah (1 Chronicles 3:17-24) in light of the tablets from Āl-Yāhūdu - Itzhak Amar (Old Testament Essays)
The genealogy of Jeconiah (1 Chr 3:17–24), as documented in the Book of Chronicles, stands as the last historical passage within the book. This genealogical record encapsulates approximately 11 successive generations, from the destruction and exile to the subsequent Persian period. In this discourse, I undertake a comparative analysis of the Midrashic interpretations of the names delineated in Jeconiah's genealogical list and those articulated in the tables from Āl-Yāhudū. The discernible correlations between these two textual sources significantly contribute to a nuanced comprehension of the challenges and aspirations experienced by those enduring the exile and those who resettled in the State of Judah. Accordingly, I posit that these intertextual connections introduce an additional dimension to the cultural milieu in which the Book of Chronicles was composed and, above all, to the question, which must have occupied the exiles: will the House of David return to its pre-destruction glory?